SISTEM INFORMASI APLIKASI PENGELOLAAN TRANSAKSI KEUANGAN DAN PENDATAAN KONSUMEN PADA CV. PUPLAS - Loveri, Tomi Tm (Jurnal Sains dan Informatika, 2018)
The author conducted research on Cv. Puplas s, aims to know about financial management and data collection of consumers inÂ  Cv. Puplas. Transaction management and report creation that is still manual and do not have a database, so often the occurrence of errors in the processing of financial transactions. Likewise, when the consumer data processing and reporting process given to the leadership takes a long time and less efficient, because the data is still in the form of archives. To overcome this problem, the writer tries to design a system that can solve the problem. This research is done using field research method with direct observation and interview, then in Library Research for Literature study and laboratory research to design Information System using Web Programing CodeIgniter and SQLyog as database manager